Association of chronic Candida albicans respiratory infection with a more severe lung disease in patients with cystic fibrosis. Issue 11 (18th September 2015) - Gileles‐Hillel, Alex; Shoseyov, David; Polacheck, Itzhack; Korem, Maya; Kerem, Eitan; Cohen‐Cymberknoh, Malena
Summary Background Despite the increase in fungal isolates, the significance of chronic Candida albicans airway colonization in CF is unclear. Aim To investigate the impact of C. albicans airway colonization on CF disease severity. Methods Longitudinal analysis of clinical data from CF patients followed during 2003–2009 at our CF center. Patients were stratified based on their C. albicans colonization status – chronic, intermittent, and none. Results A total of 4, 244 cultures were obtained from 91 patients (mean age 19.7 years, range 5–68). The three colonization groups were similar in age, gender, and body mass index (BMI). Compared to the non‐colonized group (n = 27, 30%), the chronic C. albicans colonization group (n = 34, 37%), had a significantly lower FEV1 percent predicted (74.3 ± 23.1% vs. 93.9% ± 22.2) with a higher annual rate of FEV1 decline (− 1.9 ± 4.2% vs. 0.7 ± 4.5%). The patients who were intermittently colonized with C. albicans had intermediate values. Conclusions Chronic respiratory colonization of C. albicans is associated with worsening of FEV1 in CF. Prospective studies are needed to confirm this finding and to corroborate whether indeed C. albicans drives a deleterious lung phenotype. Pediatr Pulmonol. 2015; 50:1082–1089. © 2015 Wiley Periodicals, Inc.